Cyperus prophyllatus: An endangered aquatic new species of Cyperus L. (Cyperaceae) with a exceptional spikelet disarticulation pattern among about 950 species, including molecular phylogenetic, anatomical and (micro)morphological data. - André Rodolfo de Oliveira Ribeiro; Luciana Pereira-Silva; Jéssika Paula Silva Vieira; Isabel Larridon; Vinicius Santos Ribeiro; Guilherme Felitto; Geovane Souza Siqueira; Anderson Alves-Araújo; Marccus Alves (PLoS ONE)
Cyperus prophyllatus, an endangered new species of Cyperus (Cyperaceae) from an aquatic ecosystem of the Atlantic Forest, Espírito Santo State, southeastern Brazil, is described and illustrated. The spikelet morphology of Cyperus prophyllatus is unique among the c. 950 species of Cyperus in having both a conspicuous spikelet prophyll and a corky rachilla articulation, which remain persistent at the base of the spikelet after disarticulation. Our molecular phylogenetic data support the placement of C. prophyllatus in the C3 Cyperus Grade and more precisely in the clade representing Cyperus sect. Oxycaryum, which also includes C. blepharoleptos and C. gardneri. Anatomical and (micro)morphological analyses corroborate the phylogenetic results, provide a better understanding of ecology and taxonomy, as well as reveal compatibility of structures with survival and dispersion in aquatic environments. A distribution map, table with distinctive characters of allied species, and conservation status are made available.